Capsaicin lacks tumor-promoting effects during colon carcinogenesis in a rat model induced by 1,2-dimethylhydrazine - Caetano, Brunno Felipe Ramos [UNESP]; Tablas, Mariana Baptista [UNESP]; Ignoti, Marcela Gonçalves [UNESP]; de Moura, Nelci Antunes [UNESP]; Romualdo, Guilherme Ribeiro [UNESP]; Barbisan, Luís Fernando [UNESP]; Rodrigues, Maria Aparecida Marchesan [UNESP] (Springer Nature, 2020)
Capsaicin (CPS, 8-methyl-N-vanillyl-trans-6-nonenamide), a pungent alkaloid from chili peppers, has contradictory effects in both experimental and human carcinogenesis. Thus, we evaluated the modifying effects of chronic CPS during the promotion and progression stages of rat colon carcinogenesis induced by 1,2-dimethylhydrazine (DMH). Male Wistar rats were given four subcutaneous injections of DMH (40 mg/body weight (b.w.)) twice a week, for 2 weeks. After DMH-induced tumor initiation, the animals were treated with CPS at 5 or 50 mg/kg b.w. by gavage for 24 weeks (three times a week). High-dose CPS reduced both cell proliferation in adjacent “normal-appearing” colonic crypts and the total number of preneoplastic aberrant crypt foci (ACF) but did not change the number of dysplastic ACF or ACF multiplicity. Although the proportion of adenomas was increased, and tubular adenocarcinomas decreased in high-dose CPS, both CPS interventions exerted no effects on total tumor incidence, volume, multiplicity, cell proliferation (Ki-67), and apoptosis (caspase-3). In accordance, high-dose CPS treatment had discrete effects on gene expression in colon tumors, as only 3/94 (3.19%) genes were significantly modified (downregulation of Cebpd and Fasl, and upregulation of Jag1). The findings of the present study show that CPS does not impact on the promotion/progression stages of rat colon carcinogenesis. Therefore, CPS at a high-dose intervention showed to be a safe food ingredient.
Keywords: 1,2-Dimethylhydrazine; Aberrant crypt foci and tumors; Cancer promotion and progression stages; Capsaicin; Colon carcinogenesis